Islam: a contemporary comparative discourse - Kamaruzaman, Kamar Oniah (Academy for Civilizational Studies, 2003)
An overview of Islam for contemporary society. A general comparative view with other religions is presented. The Islamic concept of religion is explained. The Pillars of Islam (Arkan al-Islam) the Pillars of Faith (Arkan al-Iman)and are also discussed. The worldview and social dimensions of Islam are also presented.